2021
DOI: 10.3389/fonc.2021.649655
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA TCF7 Promotes Epithelial Ovarian Cancer Viability, Mobility and Stemness via Regulating ITGB8

Abstract: This study aimed to investigate the carcinogenic role of long non-coding RNA T-cell factor 7 (lnc-TCF7) in epithelial ovarian cancer (EOC). Lnc-TCF7 overexpression and shRNA plasmids were transfected into SKOV3 and OVCAR3 cells, followed by measurement of cell proliferation, migration, invasion, apoptosis, stemness, and mRNA profile (via microarray). Besides, lnc-TCF7 expression was measured in tumor and adjacent tissues from 76 EOC patients. Lnc-TCF7 was upregulated in EOC cell lines; its overexpression incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The transfection of CD133+ OCSCs with LINC00115 lncRNA promoted stemness and inhibited apoptosis of OCSCs by up-regulating SOX9 and the Wnt/β-catenin pathway [ 334 ]. In SKOV3 and OVCAR3 cell cultures, the lncRNA T-cell factor-7 (lnc-TCF7) was found to be up-regulated, followed with decreased apoptosis and increased CD44, CD133 expression and CD44+CD133+ cell proportion with concomitant spheres formation efficiency and drug resistance against cisplatin [ 335 ]. In HGOC cell lines (OVCAR3, CAOV3, OVCAR5, COV362, Kuramochi), lncRNA HOTAIR was generally overexpressed, but its expression was especially up-regulated in ALDH+ OCSCs and associated with increased spheroid formation and colony forming ability [ 336 ].…”
Section: Genetic and Epigenetic Regulation Of Ocscsmentioning
confidence: 99%
“…The transfection of CD133+ OCSCs with LINC00115 lncRNA promoted stemness and inhibited apoptosis of OCSCs by up-regulating SOX9 and the Wnt/β-catenin pathway [ 334 ]. In SKOV3 and OVCAR3 cell cultures, the lncRNA T-cell factor-7 (lnc-TCF7) was found to be up-regulated, followed with decreased apoptosis and increased CD44, CD133 expression and CD44+CD133+ cell proportion with concomitant spheres formation efficiency and drug resistance against cisplatin [ 335 ]. In HGOC cell lines (OVCAR3, CAOV3, OVCAR5, COV362, Kuramochi), lncRNA HOTAIR was generally overexpressed, but its expression was especially up-regulated in ALDH+ OCSCs and associated with increased spheroid formation and colony forming ability [ 336 ].…”
Section: Genetic and Epigenetic Regulation Of Ocscsmentioning
confidence: 99%
“…LncRNA TCF7 has been found to enhance cell viability, migration, invasion via modulation of ITGB8 in epithelial ovarian cancer ( Su and Huang, 2021 ). Moreover, lncRNA TCF7 promoted the stemness of ovarian cancer cells via acceleration of spheres formation by promotion of CD44 and CD133 expression.…”
Section: Lncrnas Promote Cisplatin Resistancementioning
confidence: 99%
“…Moreover, lncRNA TCF7 promoted the stemness of ovarian cancer cells via acceleration of spheres formation by promotion of CD44 and CD133 expression. Furthermore, lncRNA TCF7 accelerated cisplatin resistance in epithelial ovarian cancer cells ( Su and Huang, 2021 ). Molecular experimental data showed that lncRNA TCF7 promoted the expression of ITGB8 and exerted its oncogenic function in ovarian cancer ( Su and Huang, 2021 ).…”
Section: Lncrnas Promote Cisplatin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Integrin α2, a direct target of miR-206, promotes TNBC self-renewal-related mammosphere formation, where canonical Wnt signaling is involved ( 189 ). Recently, a study demonstrated that upregulation of integrin β8 mediated by lnc-TCF7 leads to ovarian cancer stemness ( 190 ). Integrin αvβ8, a key activator of TGF-β, regulates immunotherapy and radiotherapy resistance, which may be reversed by a potent blocking monoclonal antibody against integrin αvβ8 (ADWA-11) in prostate cancer ( 191 ).…”
Section: Integrin and Endocrine-related Cancersmentioning
confidence: 99%